Forms of Phosphorus in relation to Soil Maturity along a Toposequence under Hot, Dry, Subhumid Agro-ecological Subregion of West Bengal - and Debashis Mandal, Dipak Sarkar, Abhijit Haldar (Journal of the Indian Society of Soil Science, 2014)
Forms of soil phosphorus (P) are characterized in relation to soil properties in five pedons belonging to Inceptisols and Alfisols, occurring along a toposequence in Hot Dry Subhumid Agroecological Subregion (AESR 12.3) of West Bengal, falling under Chotanagpur plateau region. The soils are shallow (1.5 m), sandy clay loam to clayey in texture, moderately acidic to neutral in reaction (pHaq. 5.3 – 6.6), low to high in organic carbon content, low in NaHCO3 extractable P (2.1–3.0 mg kg-1 in the surface horizon), low to medium in NH4OAc–extractable K (32.0–43.0 mg kg-1 in the surface horizon) and fairly high in Fe2O3 content (15.0-18.8%). Based upon overall profile weighted mean (PWM) values maximum amount of P is in the form of reductant soluble P (RS-P) [109.9 mg kg-1] while minimum amount is in the form of saloid P (S-P) [1.9 mg kg-1] contributing 31.2% and 0.5% to the total P content, respectively. Sequential extraction of inorganic soil P fractions reveal that the mean relative abundance follow the order: reductant soluble phosphate (RS-P) > iron phosphate (Fe-P) > occluded-P = calcium phosphate (Ca-P) > aluminium phosphate (Al-P) > saloid phosphate (S-P). The overall relative abundance of the different inorganic P fractions in terms of their average ratios are: S-P (0.1) : Al-P (0.8) : Fe-P (2.2) : Ca-P (1.0) : RS-P (6.0) : occluded-P (1.0). The PWM - total P content suggest that the soils are fairly rich in P reserve ranging from 279.3 to 533.2 mg kg-1 with an overall mean of 352.3 mg kg-1. Significant positive correlation was observed between S-P with OC (r = 0.504**) and total P (r = 0.653***). Close relationship between total P and S-P (r = 0.653***), Fe-P (r = 0.520**) suggested the existence of equilibrium between the former and the latter. The study reconfirms the poor P availability status of the soils under Chotanagpur plateau region of West Bengal. Soil maturity based upon PWM of total P is in the sequence: P5 (most matured) > P4 > P3 > P2 > P1 (least matured) which did not corroborate the maturity sequence inferred from soil taxonomy viz., P4 (most matured) > P1, P2, P3, P5 (least matured). Maturity sequence derived from weathering index (WI) based upon inorganic soil P fractions viz., P4 (most matured) > P3 > P2 > P5 > P1 (least matured) is in good agreement with that obtained from soil classification indicating a close relationship between the former and the later. The study emphasized the suitability of inorganic soil P based weathering index (WI) for adjudging soil maturity in terms of pedogenic development of the soils.